Manajemen Risiko Di Perbankan Syariah - Joko Hadi Purnomo (LPPM Institut Agama Islam Al-Hikmah Tuban, 2019)
Abstract, Risk is the possibility of an undesirable occurrence, which can cause losses if it is not anticipated or managed properly. While risk management is a series of methodologies and procedures used to identify, measure, monitor and control risks arising from all bank business activities. Risk management of Islamic banks has a different character from conventional banks, mainly because of the types of types of risks that are inherent only in bank that operates in sharia ways. The caharacteristics of risk management in Islamic banks are risk identification, risk assessment, risk anticipation and risk monitoring. Keywords: risk management, sharia, Islamic banks